Nanostructured materials for energy conversion and energy storage applications - Hong, J (2018)
Currently, fossil fuels (i.e. coal, natural gas and oil) make up a significant proportion of our global energy demands and are classified as non-renewable energy sources. It is well known that we are confronting an energy crisis due to the depletion of these fossil fuels. Furthermore, as these fuels become more expensive and harder to source, there is a considerable need for low cost and facile processing of environmentally-friendly energy sources and storage systems. Nanostructured 0-dimensional to 2-dimensional transition metal oxides and sulphides are promising materials for low-cost and high efficiency energy conversion and storage applications (especially for solar cell and supercapacitor technologies). Their unique physical and chemical properties as well the facile phase synthesis and device fabrication, demonstrate that nanostructured material-based energy sources could allow for the delivery of low cost power generation in the not too distant future. Nevertheless, further research needs to be carried out to increase the overall power conversion efficiencies of these corresponding solar cells and the specific energy storing capacitance of supercapacitors to meet the requirements for integration in commercially-available systems. This thesis is therefore focused on finding various ways to control the size and structures of transition metal oxides and sulphides to 1) understand the energy conversion and storing mechanisms in these materials and 2) to improve the overall energy conversion and storage performance. For solar cell technologies, this thesis demonstrates a promising synthetic procedure for fabricating colloidal quantum dot (CQD) structures of different sizes based upon a hot injection method and a non-hot injection method. With these synthesis methods, CQDs with a high monodispersity and different band gap properties have been prepared for use in solar cells. Moreover, for quantum dot solar cells (QDSCs), surface functionalization of CQDs is demonstrated through the precise control of a halide ligand exchange method and a hybrid ligand exchange method. It is found that changing the surface molecules on CQDs can significantly alter the electronic and optoelectronic properties, and subsequently increase the power conversion efficiency (PCE) of QDSCs. Finally, two different plasmonic nanoparticles have been employed in QDSCs. The insertion of additional plasmonic nanostructures also improves the PCE performance of QDSCs due to dual plasmonic effects, which allows for more photons to be harnessed by scattering and near-field effects. For the development of supercapacitors, different solution-based synthetic methods are proposed for the development of novel nanostructures and to understand the underlying electrochemical storage mechanisms. Different aspect ratios of one-dimensional transition metal oxides (nanostructures) can induce the different storing performance of supercapacitors, and hierarchically designed core-shell nanostructures can also result in the better charge storing properties of supercapacitors due to the enlarged surface area, high electrical conductivity and open-porous structures. Moreover, a room temperature (25 °C) and ultrafast synthesis (< 10 min) strategy is demonstrated for producing nanostructured transition metal sulphides through a simple solution-based direct synthetic method. A single crystalline 1-D nanorod electrode is synthesized directly using an ammonium sulphide solution and unique and practically designed energy storing electrodes for supercapacitors are proposed. The collective works presented in this thesis investigate various growth strategies for synthesizing nanostructured transition metal oxides and sulphides, and also demonstrate novel energy conversion and storage application with these materials. These results provide a significant step forward in the development of energy conversion and storage devices based upon nanostructured materials.